Identifying the Components of Career Crafting in Iraq’s Social Service Organizations Using a Systematic Review Method - Sabeeh Layedh, Imad; Farahi , Mohammad Mahdi; Eslami, Ghasem; Bagheri, Ruhollah (Management Strategies and Engineering Sciences, 2026)
The present study was conducted with the aim of enumerating the components of career crafting in Iraq’s social work-based organizations using a systematic review method. The philosophical foundation of the research is based on pragmatism, and a mixed-method approach combining library and field studies was employed. The research strategy included a systematic literature review in the qualitative section and a survey in the quantitative section. The study population consisted of texts related to career crafting in reputable domestic and international scientific databases from 2000 to 2024. For qualitative data analysis, the method of qualitative content analysis was applied, and the systematic review process was carried out based on the seven-step framework of Petticrew and Roberts (2007). In this regard, after the initial search and determination of keywords, the inclusion and exclusion criteria of sources were specified using the PICOS framework. In total, 54 related studies were identified and reviewed, from which 98 components were extracted. These components, after three stages of coding and categorization, were organized into 11 categories and ultimately four main dimensions of career crafting, including “cognitive re-creation,” “skills and roles re-creation,” “relationships and opportunities re-creation,” and “personal life re-creation.” For quantitative analysis, structural equation modeling was employed. Regarding the assessment of the validity and consistency of the components with the study population, considering that the measurement model coefficients of career crafting in the structural equation modeling software fell within the acceptable range in both significance and standardized states, this indicates the accuracy and reliability of the measurement tool used in the research. The high standardized coefficients demonstrate that, in the Iraqi statistical population, the selected indicators are strongly and effectively related to the concept of career crafting, and the degree of each indicator’s contribution to explaining this concept is noteworthy. On the other hand, appropriate significance coefficients (with T-values above 1.96) indicate that the statistical relationships between the indicators and the latent construct are statistically reliable, and the probability of these relationships being random is very low. In the context of Iraq’s social work organizations, this matter carries particular importance. The validity and significance of the coefficients show that the indicators used in this model accurately and meaningfully reflect the experiences and challenges of employees in these institutions. The concept of career crafting in this context is justifiable and analyzable not only theoretically but also practically through the selected indicators. The results indicate that applying these four dimensions in Iraq’s social work organizations can lead to improved career advancement, increased satisfaction, and enhanced efficiency of social workers. This study, by providing a comprehensive framework, not only contributes to the empowerment of human resources in these organizations but also paves the way for future research on career crafting in similar cultural and social contexts.